Intra-Party Crisis and Democratic Consolidation: A Study of the 2022 Abia State Peoples Democratic Party Primaries - Ndubuisi, Uchechukwu; Omeire, Charles O. (Kashere Journal of Politics and International Relations, 2025)
The correlation between the political party and political leadership recruitment in democracies has remained integral to any democracy. As such the continuous cases of intra-party crisis have been observed as a threat to the consolidation of democracy. This study focused on intra-party crisis and democratic consolidation in Nigeria with emphasis on the 2022 Peoples Democratic Party primaries in Abia State. Three research objectives, questions and three hypotheses were formulated and used to explore the subject discussed. The study relied heavily on the proposition of the conflict theory by Karl Marx and Charles Wright Mills as the theoretical framework of analysis. The study was essentially qualitative and data were generated from secondary sources such as journals and textbooks. The findings revealed that lack of internal party democracy, elite-centred control of political parties, and poor implementation of party constitution and Electoral Act are all enablers of intra-party crisis in Nigeria’s political parties, and this impact adversely on the consolidation of democracy. The study recommended that if Nigeria’s political parties must help deepen Nigeria’s democracy, internal party democracy should be promoted, the masses should have a voice in the affairs of political parties, and the dictates of the party constitution and Electoral Act must not be compromised. The study concluded that political parties remain an important institution for any democracy to succeed and the continuous cases of intra-party crises have constrained political parties from contributing to the consolidation of democracy in Nigeria.